A preparation method of lithium iron manganese phosphate, lithium iron manganese phosphate positive electrode material and application
By coating the precursor of ferromanganese oxalate and reacting with the lithium salt solution by reflux method, the problem of poor rate and circulation performance of lithium ferromanganese phosphate positive electrode material is solved, the uniformity of the material and the improvement of the pore structure are achieved, and the electrochemical performance is significantly improved.
Patent Information
- Application Number
- CN202310078009.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-02-03
AI Technical Summary
The current lithium manganese iron phosphate positive electrode materials have poor rate performance and cycle performance, and the uniformity and consistency of the material are insufficient, which affects the electrochemical performance.
The precursor of manganese oxalate is coated with ferromanganese phosphate, and reacts with the lithium salt solution through reflux method. The self-reduction effect of oxalate is used to avoid uneven distribution of external reducing agents, promote the entry of lithium salt into the material, and improve the uniformity of the material and pore structure.
It has achieved high uniformity, excellent rate performance and high cycle performance of lithium manganese iron phosphate positive electrode material, and obtained products with good crystallinity and high conductivity.
Smart Images

Figure CN116239091B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method of lithium iron manganese phosphate, a lithium iron manganese phosphate positive electrode material and applications. Background Art
[0002] In recent years, in order to alleviate environmental problems and energy crisis, it is an inevitable trend for new energy vehicles to gradually replace fuel vehicles. Lithium-ion batteries are widely used in new energy vehicles due to their high energy density, long cycle life, and no pollution. The positive electrode material is the core part of lithium-ion batteries and directly affects the performance and cost of lithium-ion batteries.
[0003] At present, the cathode materials that have been commercialized on a large scale include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide and lithium iron phosphate. Among them, lithium iron phosphate (LiFePO4) has the advantages of low cost, high safety and good stability. The industrial production process of LiFePO4 cathode materials is very mature, and the market application is growing rapidly. However, its olivine structure determines that the voltage platform is 3.4V. The specific capacity of the cathode materials currently produced is close to the theoretical value (170mAh / g), and there is a problem of low energy density. In order to meet the requirements of high energy density power batteries, the energy density of cathode materials needs to be improved.
[0004] Lithium iron manganese phosphate (LiMn x Fe 1-x PO4) can increase the voltage platform of the positive electrode material to 4.1V, and its energy density is about 15% higher than that of lithium iron phosphate. However, the lower ion diffusion coefficient and conductivity of lithium iron phosphate restrict its further development. The coprecipitation method is a more commonly used preparation method for lithium iron phosphate. The obtained positive electrode material has a dense and compact structure. When it is subsequently mixed and roasted with lithium, lithium cannot enter the interior, and the uniformity and consistency of the material are poor, which affects the electrochemical performance of the material.
[0005] The reflux method for preparing lithium manganese iron phosphate is a process that is easy to operate, low in cost, and has high material utilization. However, when divalent iron is selected as the iron source, there is a problem of easy oxidation, which is not conducive to the uniformity of the process. When trivalent manganese iron phosphate is used as a precursor, there is a problem that iron phosphate is difficult to be uniformly reduced, resulting in poor product rate performance. Therefore, the current reflux method for preparing lithium manganese iron phosphate is difficult to obtain a product with relatively ideal rate performance and cycle performance.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a preparation method of lithium iron manganese phosphate, a lithium iron manganese phosphate positive electrode material and application, aiming to improve the uniformity of the positive electrode material product and improve the rate performance and cycle performance of the product.
[0008] The present invention is achieved in that:
[0009] In a first aspect, the present invention provides a method for preparing lithium manganese iron phosphate, comprising: mixing a manganese iron phosphate precursor coated with manganese iron oxalate with a lithium salt solution for reaction.
[0010] In an optional embodiment, the ferromanganese oxalate is coated on the ferromanganese phosphate precursor by a coprecipitation method;
[0011] Preferably, the preparation process of the ferromanganese phosphate precursor coated with ferromanganese oxalate comprises: mixing and dissolving an iron source and a manganese source to obtain an iron-manganese mixed solution, mixing the iron-manganese mixed solution with a suspension formed by the ferromanganese phosphate precursor and oxalate, and obtaining the ferromanganese phosphate precursor coated with ferromanganese oxalate after the precipitation reaction is completed;
[0012] Preferably, the amount of oxalate is adjusted so that the molar ratio of ferromanganese phosphate to ferromanganese oxalate is 2:1.0-1.2.
[0013] In an optional embodiment, an iron source and a manganese source are mixed and dissolved under an inert atmosphere to obtain an iron-manganese mixed solution, a ferromanganese phosphate precursor is mixed with water to obtain a ferromanganese phosphate precursor suspension, and the iron-manganese mixed solution, the ferromanganese phosphate precursor suspension and oxalate are mixed to perform a precipitation reaction;
[0014] Preferably, the concentration of iron in the iron-manganese mixed solution is controlled to be 0.08 mol / L-0.13 mol / L, and the molar ratio of iron to manganese is 1:1.4-1.6; the amount of oxalate added is adjusted so that the molar ratio of oxalate ions to the total amount of iron and manganese is 1-1.5:1;
[0015] Preferably, the iron source is selected from at least one of ferrous sulfate, ferrous nitrate, ferric chloride and ferric acetate;
[0016] Preferably, the manganese source is selected from at least one of manganese sulfate, manganese acetate and manganese chloride;
[0017] Preferably, the oxalate is selected from ammonium oxalate, sodium oxalate and potassium oxalate;
[0018] Preferably, the ferromanganese phosphate precursor suspension is obtained by mixing a ferromanganese phosphate precursor with a particle size of 300nm-500nm and water, and the concentration of the suspension is 50mg / mL-100mg / mL.
[0019] In an optional embodiment, the ferromanganese phosphate precursor coated with ferromanganese oxalate is mixed with a lithium salt solution for reflux reaction;
[0020] Preferably, during the reflux reaction, the reaction temperature is controlled to be 100°C-200°C, and the reaction time is 8h-24h;
[0021] Preferably, the pH value of the control system is 4-5;
[0022] Preferably, the molar ratio of the lithium salt to the manganese ferrophosphate precursor coated with manganese ferrooxalate is controlled to be 1-1.5:1.
[0023] In an optional embodiment, the lithium salt solution is prepared by mixing a lithium source, water and phosphoric acid, and the concentration of lithium in the lithium salt solution is controlled to be 0.2 mol / L-0.3 mol / L;
[0024] Preferably, the lithium source is lithium phosphate, and the molar ratio of lithium phosphate to phosphoric acid is controlled to be 1:1.5-2.5.
[0025] In an optional embodiment, the method further comprises: performing solid-liquid separation, washing and drying the obtained slurry after the reflux reaction to obtain a lithium iron manganese phosphate composite material, and calcining the lithium iron manganese phosphate composite material;
[0026] Preferably, the solid-liquid separation method is centrifugation, the centrifugal speed is controlled to be 8000r / min-10000r / min, and the centrifugal time is 10min-15min;
[0027] Preferably, the washing method is to wash with water and organic solvent alternately for multiple times;
[0028] Preferably, the drying temperature is controlled to be 80° C.-120° C., and the drying time is 12 h-24 h.
[0029] In an optional embodiment, the calcination temperature is controlled to be 500° C.-800° C., and the calcination time is 6 h-24 h;
[0030] Preferably, the calcination process is carried out under an inert atmosphere.
[0031] In a second aspect, the present invention provides a lithium manganese iron phosphate positive electrode material prepared by any one of the preparation methods in the aforementioned embodiments.
[0032] In a third aspect, the present invention provides a lithium iron manganese phosphate positive electrode plate prepared from the lithium iron manganese phosphate positive electrode material of the aforementioned embodiment.
[0033] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the lithium iron manganese phosphate positive electrode sheet of the aforementioned embodiment.
[0034] The present invention has the following beneficial effects: when the ferromanganese phosphate precursor is coated with ferromanganese oxalate, no external reducing agent is required when the ferromanganese phosphate lithium positive electrode material is prepared by the reflux method, thereby avoiding the problem of uneven distribution of the reducing agent. The present invention utilizes the reducing effect of the oxalate radicals in the precursor to make the reduction more uniform and sufficient. In addition, the porous structure generated by the decomposition of oxalate radicals during the reaction can prevent a large number of bubbles from being generated by overboiling, causing the adsorbed lithium source to fall off, and promote the lithium salt to enter the interior of the particles. The uniformity is high, and the pore structure can also improve the lithium ion diffusion rate and conductivity, thereby obtaining a product with good crystallinity, excellent rate performance, and high cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 This is the XRD diagram of lithium manganese iron phosphate obtained by uniform reduction in Example 1;
[0037] Figure 2 This is the XRD pattern of lithium manganese iron phosphate prepared in Comparative Example 1. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] The present invention provides a method for preparing lithium manganese iron phosphate, comprising the following steps:
[0040] S1. Preparation of ferromanganese phosphate precursor coated with ferromanganese oxalate
[0041] Ferromanganese oxalate is coated on the ferromanganese phosphate precursor to obtain a ferromanganese oxalate-coated ferromanganese phosphate precursor for subsequent reflux reaction.
[0042] Specifically, the preparation process of the ferromanganese phosphate precursor can adopt the existing process, such as reference to CN109103452A.
[0043] In some embodiments, the preparation process of the ferromanganese phosphate precursor coated with ferromanganese oxalate includes: mixing and dissolving an iron source and a manganese source to obtain an iron-manganese mixed solution, mixing the iron-manganese mixed solution with a suspension formed by the ferromanganese phosphate precursor and oxalate, and obtaining the ferromanganese phosphate precursor coated with ferromanganese oxalate after the precipitation reaction is completed. The precipitation reaction is carried out at room temperature, and the reaction temperature can be 20°C-30°C. During the reaction, oxalate reacts with the iron source and the manganese source to generate ferromanganese oxalate coated on the ferromanganese phosphate precursor.
[0044] In actual operation, the iron source and the manganese source are mixed and dissolved in an inert atmosphere to obtain an iron-manganese mixed solution, the ferromanganese phosphate precursor is mixed with water to obtain a ferromanganese phosphate precursor suspension, and the iron-manganese mixed solution, the ferromanganese phosphate precursor suspension and oxalate are mixed to perform a precipitation reaction. Mixing under an inert gas can prevent the oxidation of ferrous ions and ensure the purity of the product.
[0045] Specifically, the type of inert gas is not limited, and it may be nitrogen, argon, etc.
[0046] In order to make the reaction of generating ferromanganese oxalate sufficient and control the coating amount of ferromanganese oxalate at the same time, the inventors optimized the operating parameters in the preparation process: the concentration of iron in the iron-manganese mixed solution was controlled to be 0.08 mol / L-0.13 mol / L, and the molar ratio of iron to manganese was 1:1.4-1.6; by adjusting the amount of oxalate added, the molar ratio of oxalate ions to the total amount of iron and manganese was 1-1.5:1, and the molar ratio of ferromanganese phosphate to ferromanganese oxalate was controlled to be 2:1.0-1.2.
[0047] It should be noted that the amount of oxalate used directly affects the coating amount of manganese iron oxalate. It is appropriate to control the molar ratio of manganese iron phosphate and manganese iron oxalate to 2:1.0-1.2. Within this range, the rate performance and cycle performance of the prepared lithium manganese iron phosphate can be better.
[0048] Specifically, the concentration of iron in the iron-manganese mixed solution can be 0.08 mol / L, 0.1 mol / L, 0.13 mol / L, etc.; the molar ratio of iron to manganese can be 1:1.4, 1:1.5, 1:1.6, etc.; the amount of oxalate added is to control the molar ratio of oxalate ions to the total amount of iron and manganese, which can be 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc.; the molar ratio of ferromanganese phosphate to ferromanganese oxalate can be 2:1.0, 2:1.1, 2:1.2, etc. The pH value of the iron-manganese mixed solution can be roughly controlled at about 4.
[0049] In some embodiments, the iron source is selected from at least one of ferrous sulfate, ferrous nitrate, ferric chloride and ferric acetate; the manganese source is selected from at least one of manganese sulfate, manganese acetate and manganese chloride; and the oxalate is selected from ammonium oxalate, sodium oxalate and potassium oxalate. The iron source, manganese source and oxalate are not limited to the above raw materials. Under the premise that the reaction principle can be realized, other raw materials can be selected, which is not limited here.
[0050] In some embodiments, the manganese iron phosphate precursor suspension is obtained by mixing a manganese iron phosphate lithium precursor with a particle size of 300nm-500nm (such as 300nm, 400nm, 500nm, etc.) and water, and the concentration of the suspension is 50mg / mL-100mg / mL, such as 50mg / mL, 60mg / mL, 70mg / mL, 80mg / mL, 90mg / mL, 100mg / mL, etc.
[0051] S2. Reflux reaction
[0052] The method of mixing the ferromanganese phosphate precursor coated with ferromanganese oxalate with a lithium salt solution for reflux reaction, and preparing the lithium ferromanganese phosphate positive electrode material by reflux reaction of the ferromanganese phosphate precursor coated with ferromanganese oxalate and a lithium source has the following advantages:
[0053] (1) No external reducing agent is required, thus avoiding the problem of uneven distribution of reducing agents. The reduction effect of the oxalate ions in the precursor is utilized to make the reduction more uniform and sufficient.
[0054] (2) The porous structure produced by the decomposition of oxalate can prevent overboiling from generating a large number of bubbles that would cause the adsorbed lithium source to fall off, thereby promoting the entry of lithium salts into the particles with high uniformity. The pore structure can also increase the lithium ion diffusion rate and conductivity, thereby obtaining a product with good crystallinity, excellent rate performance, and high cycle performance.
[0055] (3) The preparation method has good controllability and can effectively regulate the structure and performance of lithium manganese iron phosphate to obtain products with stable quality.
[0056] In some embodiments, during the reflux reaction, the reaction temperature is controlled to be 100°C-200°C, the reaction time is 8h-24h, and the pH value of the system is controlled to be 4-5, and the reaction temperature, time and pH value are controlled to allow the reaction to proceed fully. During the reflux reaction, lithium phosphate reacts with manganese iron oxalate, the released oxalate reduces the trivalent iron, and a porous structure is formed to facilitate the entry of lithium ions to form lithium manganese iron phosphate.
[0057] Specifically, the reaction temperature can be 100°C, 150°C, 200°C, etc., the reaction time can be 8h, 10h, 12h, 15h, 18h, 20h, 24h, etc., and the pH value can be 4.0, 4.5, 5.0, etc.
[0058] In some embodiments, the lithium salt solution is a mixture of a lithium source, water and phosphoric acid, the concentration of lithium in the lithium salt solution is controlled to be 0.2 mol / L-0.3 mol / L, the lithium source is lithium phosphate, and the molar ratio of lithium phosphate to phosphoric acid is controlled to be 1:1.5-2.5. Specifically, the concentration of lithium in the lithium salt solution can be 0.20 mol / L, 0.22 mol / L, 0.24 mol / L, 0.26 mol / L, 0.28 mol / L, 0.30 mol / L, etc., and the molar ratio of lithium phosphate to phosphoric acid can be 1:1.5, 1:2.0, 1:2.5.
[0059] In some embodiments, the amount of the ferromanganese phosphate precursor coated with ferromanganese oxalate is used to control the molar ratio of lithium salt to the ferromanganese phosphate precursor coated with ferromanganese oxalate to be 1-1.5:1, such as 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc.
[0060] S3, post-processing
[0061] After the reflux reaction, the obtained slurry is subjected to solid-liquid separation, washing and drying to obtain a manganese iron phosphate lithium composite material, and the manganese iron phosphate lithium composite material is calcined. The crystallinity of the product can be increased by calcination, which is conducive to further improving the performance of the product.
[0062] In some embodiments, the calcination temperature is controlled to be 500°C-800°C, and the calcination time is 6h-24h to ensure the crystallinity of the product. Specifically, the calcination temperature can be 500°C, 600°C, 700°C, 800°C, etc., and the calcination time can be 6h, 10h, 15h, 20h, 24h, etc. The calcination process is preferably carried out under an inert atmosphere to avoid interference from oxygen, and the inert gas can be nitrogen, argon, etc.
[0063] In some embodiments, the solid-liquid separation method is centrifugation, and the centrifugal speed is controlled to be 8000r / min-10000r / min, and the centrifugal time is 10min-15min, so as to fully separate the solid product. Specifically, the centrifugal speed can be 8000r / min, 9000r / min, 10000r / min, etc., and the centrifugal time can be 10min, 11min, 12min, 13min, 14min, 15min, etc.
[0064] In some embodiments, the washing method is to wash alternately with water and organic solvent for multiple times. The type of organic solvent is not limited, such as but not limited to anhydrous ethanol, and the number of washing times is not limited, such as 3 times or more.
[0065] In some embodiments, the drying is carried out at a temperature of 80°C to 120°C and a drying time of 12h to 24h. The drying process can be carried out in a general vacuum drying oven, and the drying temperature can be 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the drying time can be 12h, 15h, 20h, 24h, etc.
[0066] The embodiment of the present invention also provides a lithium manganese iron phosphate positive electrode material, which is prepared by the above preparation method and has the advantages of good product uniformity, and also excellent rate performance and cycle performance.
[0067] It should be added that the lithium iron manganese phosphate positive electrode material can be used to prepare a lithium iron manganese phosphate positive electrode sheet using a conventional method, and further combined with a cathode, an electrolyte, etc. to form a complete lithium ion battery. By improving the performance of the positive electrode material, the performance of the lithium iron manganese phosphate positive electrode material and the lithium ion battery can be further improved.
[0068] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0069] It should be added that the preparation process of the ferromanganese phosphate precursor used in the following examples is as follows:
[0070] Disperse 0.06 mol of ferric chloride and 0.24 mol of manganese chloride in water to form solution A, disperse 0.3 mol of ammonium phosphate in water to form solution B, and use 90 mL of water in total. Set the stirring speed to 800 r / min, add solution B dropwise to solution A, continue stirring for 10 min, adjust the pH of the system to 4-5 with nitric acid, continue stirring for 20 min, transfer the mixed solution to a reactor and keep it at 150°C for 10 h, cool it, wash and filter it repeatedly with deionized water and ethanol until the pH of the filtrate is neutral, and dry it at 80°C for 6 h to obtain a manganese iron phosphate precursor.
[0071] Example 1
[0072] This embodiment provides a method for preparing lithium manganese iron phosphate, comprising the following steps:
[0073] (1) Preparation of ferromanganese phosphate precursor coated with ferromanganese oxalate
[0074] The nano-manganese ferrophosphate precursor with a particle size of 300-500 nm was crushed by ball milling, and then mixed with water to form a suspension with a concentration of 100 mg / mL.
[0075] Ferrous sulfate and manganese sulfate were dissolved in water under nitrogen atmosphere to obtain an iron-manganese mixed solution, and the pH value was adjusted to 4. In the iron-manganese mixed solution, the iron ion concentration was 0.1 mol / L and the manganese ion concentration was 0.15 mol / L. 1L of the iron-manganese mixed solution was taken, 0.5 mol of ferromanganese phosphate precursor was added, and then 0.3 mol of ammonium oxalate was added. After precipitation was completed at room temperature (20°C, the same below), ferromanganese oxalate-coated ferromanganese phosphate was obtained.
[0076] (2) Reflux reaction
[0077] 11.6 g of lithium phosphate was dispersed in 500 mL of deionized water, and 17 mL of phosphoric acid (85% phosphoric acid) was added to obtain a lithium salt solution.
[0078] 0.1 mol of ferromanganese phosphate precursor coated with ferromanganese oxalate was added to the above lithium salt solution, and refluxed at 200° C. for 8 h.
[0079] (3) Post-processing
[0080] The reflux reaction slurry was centrifuged at 8000 r / min for 15 min, washed alternately with deionized water and anhydrous ethanol for 3 times, and dried at 80° C. for 24 h. The lithium manganese iron phosphate obtained by the reflux reaction was calcined at 500° C. for 24 h in a nitrogen atmosphere to obtain a lithium manganese iron phosphate positive electrode material.
[0081] The XRD pattern of the positive electrode material prepared in Test Example 1 is as follows: Figure 1 The prepared lithium manganese iron phosphate corresponds to the standard card and has good crystallinity.
[0082] After testing, the obtained positive electrode material has a discharge capacity of 154.3 mAh / g at a rate of 0.1C, and a capacity retention rate of 91.9% after 100 cycles.
[0083] Example 2
[0084] This embodiment provides a method for preparing lithium manganese iron phosphate, comprising the following steps:
[0085] (1) Preparation of ferromanganese phosphate precursor coated with ferromanganese oxalate
[0086] The nano-manganese ferrophosphate precursor with a particle size of 300-500 nm was crushed by ball milling, and then mixed with water to form a suspension with a concentration of 50 mg / mL.
[0087] Ferrous sulfate and manganese sulfate were dissolved in water under nitrogen atmosphere to obtain an iron-manganese mixed solution, and the pH value was adjusted to 4. In the iron-manganese mixed solution, the iron ion concentration was 0.1 mol / L, and the manganese ion concentration was 0.15 mol / L.
[0088] Take 1L of iron-manganese mixed solution, add 0.5mol of ferromanganese phosphate precursor, and then add 0.3mol of ammonium oxalate. After precipitation at room temperature (20°C, the same below), ferromanganese oxalate-coated ferromanganese phosphate is obtained.
[0089] (2) Reflux reaction
[0090] 14 g of lithium phosphate was dispersed in 500 mL of deionized water, and 20.8 mL of phosphoric acid (85% phosphoric acid) was added to obtain a lithium salt solution.
[0091] 0.1 mol of ferromanganese phosphate precursor coated with ferromanganese oxalate was added to the above lithium salt solution, and refluxed at 100° C. for 24 hours.
[0092] (3) Post-processing
[0093] The reflux reaction slurry was centrifuged at 10000 r / min for 10 min, washed alternately with deionized water and anhydrous ethanol for 3 times, and dried at 120° C. for 12 h. The lithium manganese iron phosphate obtained by the reflux reaction was calcined at 800° C. for 6 h in a nitrogen atmosphere to obtain a lithium manganese iron phosphate positive electrode material.
[0094] After testing, the obtained positive electrode material has a discharge capacity of 152.8 mAh / g at a rate of 0.1C, and a capacity retention rate of 92.8% after 100 cycles.
[0095] Example 3
[0096] This embodiment provides a method for preparing lithium manganese iron phosphate, comprising the following steps:
[0097] (1) Preparation of ferromanganese phosphate precursor coated with ferromanganese oxalate
[0098] The nano-manganese ferrophosphate precursor with a particle size of 300-500 nm was crushed by ball milling, and then mixed with water to form a suspension with a concentration of 80 mg / mL.
[0099] Ferrous sulfate and manganese sulfate were dissolved in water under nitrogen atmosphere to obtain an iron-manganese mixed solution, and the pH value was adjusted to 4. In the iron-manganese mixed solution, the iron ion concentration was 0.1 mol / L, and the manganese ion concentration was 0.15 mol / L.
[0100] Take 1L of the iron-manganese mixed solution, add 0.6mol of ferromanganese phosphate precursor, and then add 0.3mol of ammonium oxalate. After precipitation at room temperature (20°C, the same below), ferromanganese oxalate-coated ferromanganese phosphate is obtained.
[0101] (2) Reflux reaction
[0102] 17.4 g of lithium phosphate was dispersed in 500 mL of deionized water, and 25.8 mL of phosphoric acid (85% phosphoric acid) was added to obtain a lithium salt solution.
[0103] 0.1 mol of ferromanganese phosphate precursor coated with ferromanganese oxalate was added to the above lithium salt solution, and reflux reaction was carried out at 150° C. for 12 hours.
[0104] (3) Post-processing
[0105] The reflux reaction slurry was centrifuged at 9000 r / min for 15 min, washed alternately with deionized water and anhydrous ethanol for 3 times, and dried at 100° C. for 12 h. The lithium manganese iron phosphate obtained by the reflux reaction was calcined at 650° C. for 12 h in a nitrogen atmosphere to obtain the lithium manganese iron phosphate positive electrode material.
[0106] After testing, the obtained positive electrode material has a discharge capacity of 153.6 mAh / g at a rate of 0.1C, and a capacity retention rate of 92.2% after 100 cycles.
[0107] Comparative Example 1
[0108] This comparative example provides a method for preparing lithium manganese iron phosphate, comprising the following steps:
[0109] (1) 11.6 g of lithium phosphate and 18.0 g of ascorbic acid were dispersed in 500 mL of deionized water, and 17 mL of phosphoric acid (85% phosphoric acid) was added and stirred to obtain a mixed solution.
[0110] (2) 0.1 mol of manganese iron phosphate precursor was added to the mixed solution and refluxed at 200° C. for 8 h.
[0111] (3) The reflux reaction slurry was centrifuged at 8000 r / min for 15 min, washed alternately with deionized water and anhydrous ethanol for 3 times, and dried at 80° C. for 24 h.
[0112] (4) The lithium manganese iron phosphate obtained by the reflux reaction is calcined at 500° C. for 24 hours in an inert atmosphere to obtain a lithium manganese iron phosphate positive electrode material.
[0113] Note: The main difference between Comparative Example 1 and Example 1 is that ferromanganese oxalate is not introduced, but a reducing agent is used.
[0114] The XRD spectrum of the positive electrode material prepared in the test comparative example is as follows: Figure 2 As shown. Its XRD spectrum only shows a few characteristic peaks of lithium manganese iron phosphate, and the peak intensity is not high, and there are many impurity peaks that are not intercalated with lithium and not uniformly reduced. This shows that ordinary manganese iron phosphate cannot be uniformly reduced and cannot be well intercalated with lithium and crystallized, resulting in low crystallinity of the material and many impurity peaks.
[0115] After testing, the obtained positive electrode material has a discharge capacity of 138.5 mAh / g at a rate of 0.1C, and a capacity retention rate of 85.5% after 100 cycles.
[0116] Comparative Example 2
[0117] The only difference from Example 1 is that the amount of ammonium oxalate used is 0.2 mol, and the specific steps are as follows:
[0118] Ferrous sulfate and manganese sulfate were dissolved in water under nitrogen atmosphere to obtain an iron-manganese mixed solution, and the pH value was adjusted to 4. In the iron-manganese mixed solution, the iron ion concentration was 0.08 mol / L, and the manganese ion concentration was 0.12 mol / L.
[0119] Take 1L of iron-manganese mixed solution, add 0.5mol of ferromanganese phosphate precursor, and then add 0.2mol of ammonium oxalate. After precipitation at room temperature (20°C, the same below), ferromanganese oxalate coated ferromanganese phosphate is obtained. The molar ratio of the core ferromanganese phosphate to the coating layer ferromanganese oxalate of the obtained material is 2.5:1, and the oxalate ion is not enough to reduce the trivalent iron.
[0120] After testing, the obtained positive electrode material has a discharge capacity of 136.4 mAh / g at a rate of 0.1C, and a capacity retention rate of 85.2% after 100 cycles.
[0121] Comparative Example 3
[0122] The only difference from Example 1 is that the amount of ammonium oxalate used is 0.48 mol.
[0123] Ferrous sulfate and manganese sulfate were dissolved in water under nitrogen atmosphere to obtain an iron-manganese mixed solution, and the pH value was adjusted to 4. In the iron-manganese mixed solution, the iron ion concentration was 0.2 mol / L, and the manganese ion concentration was 0.28 mol / L.
[0124] Take 1L of iron-manganese mixed solution, add 0.5mol of ferromanganese phosphate precursor, and then add 0.48mol of ammonium oxalate. After precipitation at room temperature (20°C), ferromanganese phosphate coated with ferromanganese oxalate is obtained. The molar ratio of the core ferromanganese phosphate to the coating layer of ferromanganese oxalate in the obtained material is 1.04:1. The oxalate radical is excessive, and the porous structure is affected when it is decomposed.
[0125] After testing, the obtained positive electrode material has a discharge capacity of 137.5 mAh / g at a rate of 0.1C, and a capacity retention rate of 83.2% after 100 cycles.
[0126] It can be seen from Comparative Examples 2 and 3 that if the amount of ammonium oxalate used is too large or too small, the capacity of the product will decrease and the cycle performance will decrease.
[0127] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing lithium manganese iron phosphate, characterized in that: include: The ferromanganese phosphate precursor coated with ferromanganese oxalate is mixed with a lithium salt solution for reaction; The invention discloses a method for coating ferromanganese oxalate on a ferromanganese phosphate precursor by a coprecipitation method. The preparation process of the ferromanganese phosphate precursor coated with ferromanganese oxalate comprises: mixing and dissolving an iron source and a manganese source under an inert atmosphere to obtain an iron-manganese mixed solution, mixing the ferromanganese phosphate precursor with water to obtain a ferromanganese phosphate precursor suspension, mixing the iron-manganese mixed solution, the ferromanganese phosphate precursor suspension and the oxalate to carry out a precipitation reaction; after the precipitation reaction is completed, the ferromanganese phosphate precursor coated with ferromanganese oxalate is obtained; by adjusting the amount of the oxalate, the molar ratio of ferromanganese phosphate to ferromanganese oxalate is 2:1.0-1.2; controlling the concentration of iron in the iron-manganese mixed solution to be 0.08 mol / L-0.13 mol / L, and the molar ratio of iron to manganese to be 1:1.4-1.6; by adjusting the amount of the oxalate added, the molar ratio of oxalate ions to the total amount of iron and manganese is 1-1.5:1; The ferromanganese phosphate precursor coated with ferromanganese oxalate is mixed with a lithium salt solution for reflux reaction; during the reflux reaction, the reaction temperature is controlled to be 100° C.-200° C., and the reaction time is 8 h-24 h; the pH value of the system is controlled to be 4-5; and the molar ratio of the lithium salt to the ferromanganese phosphate precursor coated with ferromanganese oxalate is controlled to be 1-1.5:1; The lithium salt solution is prepared by mixing a lithium source, water and phosphoric acid, and the concentration of lithium element in the lithium salt solution is controlled to be 0.2 mol / L-0.3 mol / L.
2. The preparation method according to claim 1, characterized in that: The iron source is selected from at least one of ferrous sulfate, ferrous nitrate, ferric chloride and ferric acetate.
3. The preparation method according to claim 1, characterized in that: The manganese source is selected from at least one of manganese sulfate, manganese acetate and manganese chloride.
4. The preparation method according to claim 1, characterized in that: The oxalate is selected from ammonium oxalate, sodium oxalate and potassium oxalate.
5. The preparation method according to claim 1, characterized in that: The ferromanganese phosphate precursor suspension is obtained by mixing a ferromanganese phosphate precursor with a particle size of 300nm-500nm and water, and the concentration of the suspension is 50mg / mL-100mg / mL.
6. The preparation method according to claim 1, characterized in that: The lithium source is lithium phosphate, and the molar ratio of lithium phosphate to phosphoric acid is controlled to be 1:1.5-2.
5.
7. The preparation method according to claim 1, characterized in that: Also includes: After the reflux reaction, the obtained slurry is subjected to solid-liquid separation, washing and drying to obtain a lithium manganese iron phosphate composite material, and the lithium manganese iron phosphate composite material is calcined.
8. The preparation method according to claim 7, characterized in that: The solid-liquid separation method is centrifugation, the centrifugal speed is controlled to be 8000r / min-10000r / min, and the centrifugal time is 10min-15min.
9. The preparation method according to claim 7, characterized in that: The washing method is to wash with water and organic solvent alternately for multiple times.
10. The preparation method according to claim 7, characterized in that: The drying process is performed at a temperature of 80° C. to 120° C. and a drying time of 12 h to 24 h.
11. The preparation method according to claim 7, characterized in that: The calcination temperature is controlled at 500°C-800°C and the calcination time is controlled at 6h-24h.
12. The preparation method according to claim 7, characterized in that: The calcination process is carried out under an inert atmosphere.
13. A lithium manganese iron phosphate positive electrode material, characterized in that: The composition is prepared by the preparation method according to any one of claims 1 to 12.
14. A lithium manganese iron phosphate positive electrode plate, characterized in that: Prepared from the lithium manganese iron phosphate positive electrode material described in claim 13.
15. A lithium ion battery, characterized in that: Including the lithium manganese iron phosphate positive electrode plate as described in claim 14.
Citation Information
Patent Citations
Preparation method of nanometer lithium ferromanganese phosphate cathode composite
CN109103452A
Lithium ion battery positive electrode material lithium iron manganese phosphate and liquid phase preparation method thereof
CN104577114A
Carbon-coated lithium manganese ferric phosphoric acid cathode material and preparation method
CN105047922A